2022
DOI: 10.4103/jfmpc.jfmpc_1268_21
|View full text |Cite
|
Sign up to set email alerts
|

The need for physical medicine and rehabilitation as an integral component in the medical education curriculum in India

Abstract: Enhanced quality of health care and increased life expectancy come with issues about the quality of life. This challenge is especially relevant to physical medicine and rehabilitation (PM and R)—a specialty focused on enhancing the quality of life. With the increasing burden of chronic diseases and disabling conditions, requirement for PM and R specialists will increase. This narrative review discusses the changing demographics, the disability trends, and the unmet needs both at present and anticipated in futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…7 Limited formal training on PR for HCP and a resulting small proportion of physiotherapists opting for cardiopulmonary specialty further contributes to this challenge. 12 , 13 While PR benefits are widely accepted in high income countries, there is a dearth of evidence from the Indian healthcare setting. Only two studies identified the benefits of PR in a systematic review in LMICs, both were classified as being at moderate risk of bias.…”
Section: Introductionmentioning
confidence: 99%
“…7 Limited formal training on PR for HCP and a resulting small proportion of physiotherapists opting for cardiopulmonary specialty further contributes to this challenge. 12 , 13 While PR benefits are widely accepted in high income countries, there is a dearth of evidence from the Indian healthcare setting. Only two studies identified the benefits of PR in a systematic review in LMICs, both were classified as being at moderate risk of bias.…”
Section: Introductionmentioning
confidence: 99%